"Determination of antioxidant content in synthetic rubber by high-performance liquid chromatography gradient elution method" - "SONG Jie-rui, LI Xiao-yin, ZHAO Hui-hui, LIU Zhi-hui, CHEN Hai-hua, WANG Zhen, LIU Sui-bo, QIN Peng, WANG Chun-long, HUANG Shi-ying" (Hecheng xiangjiao gongye)
The content of antioxidant in synthetic rubber was determined by high-performance liquid chromatography gradient elution method, the effects of the factors, such as detection wavelength, flow rate, gradient elution condition on the determination results were investigated, and the repeatability and spiked recovery rate of the method were also determined. The results showed that the optimal detection wavelength for this method was 292 nm or 285 nm and the flow rate was 1 mL/min; antioxidants had a good linear relationship within the corresponding concentration range and the calculation method was standard curve method or single-point method; this method had good repeatability and a high spiked recovery rate ranging from 90% to 101%, and all the relative standard deviations were less than 5%.